Modelling and analysis of factors affecting information perception quality of intelligent vehicle visual environment. (5th August 2019) - Huang, Zichao; Li, Bin; Ma, Yulin; Song, Xianghui; Sun, Ling
When the existing methods are used to analyse the factors affecting the perception quality of visual environment information of intelligent vehicles, the rationality of the quality evaluation index is poor and the accuracy of the evaluation result is low. A modelling method is proposed to analyse the influencing factors of information perception quality of intelligent vehicle visual environment, and the process of intelligent vehicles acquiring information through visual perception technology. The hierarchical structure model is established based on the selected information quality assessment index, and the fuzzy analytic hierarchy process is used to calculate the weight of the influencing factors, and the impact model of the perception information quality of the intelligent vehicle visual environment is constructed based on the calculation results. The experimental results show that the reasonability of the quality evaluation index of the proposed method is high and the accuracy of the evaluation results is high.